Can red cell indices predict retinopathy of prematurity in preterm extreme low birth weight neonates? A single center retrospective study - Roshan, Reashma; Shah, Mubashir H. (International Journal of Research in Medical Sciences, 2022)
Background: Improvement in neonatal health care services has led to the survival of extreme low birth weight babies over the years. This has led to increased number of retinopathy of prematurity (ROP) cases being diagnosed. Thus it becomes imperative to identify factors which can reliably predict preterm neonates at increased risk of ROP. Aims and objectives were to identify red cell indices at 4 weeks postpartum which can predict ROP in extreme low birth weight neonates. Methods: Three years ROP data in extremely low birth weight neonates was retrospectively collected and analyzed. Results: The mean gestational age at birth of the neonates in ROP group (n=149) and no-ROP group (n=191) was 28.25 (±2.71) weeks and 31.82 (±2.24) weeks, respectively (p<0.05). The mean birth weight of the neonates in ROP group and no-ROP group was 756.44 (±95.50) grams and 890 (±109.20) grams, respectively (p<0.05). In extremely low birth weight (ELBW) neonates, hematologic parameters such as hemoglobin, hematocrit, red blood cells, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration values were lower and white blood cell count was higher in ROP group as compared to no-ROP group (p<0.05). Conclusions: Red cell indices may predict which extreme low birth weight neonates are at increased risk of developing retinopathy of prematurity. Being easily and widely available, red cell indices can be used as a screening test to predict ROP.